Extensive chest wall tissue loss and its management by vertical rectus abdominis myocutaneous flap - Sandip Kanti Basu; Jayanta Bain; Debarati Chattopadhyay; Bijay Kumar Majumdar (Wolters Kluwer Medknow Publications, 2017)
Extensive electric burn around the chest in children is rare and this type of injury always poses a great challenge for its management. A 12-year-old male child with extensive electric burn of the chest wall was admitted to hospital. It was a neglected case of 9 days old burn; the young boy was in critical condition having systemic features of toxemia with widespread necrosis of the skin, subcutaneous tissues, and muscles along with exposed bones (ribs and sternum) with the risk of impending rupture of pleura through the exposed intercostal spaces. After initial resuscitation, a thorough debridement of all necrotic tissues was done. Thereafter, a superiorly based vertical rectus abdominis myocutaneous flap was harvested to cover the exposed bones and intercostal spaces. The remaining raw areas were skin grafted. The child made an excellent recovery with good outcome.